Foot Morphology and Substrate Adhesion in the Madagascan Hissing Cockroach, Gromphadorhina portentosa - van Casteren, Adam (University of Wisconsin Library, 2010)

(untitled)
Insects are successful terrestrial organisms able to locomote over a wide range of obstacles and substrates. This study investigated how foot morphology (tarsal structure) correlates with substrate adhesion and ecological niche in the Madagascan hissing cockroach, Gromphadorhina portentosa Schaum (Blattaria: Blaberidae). Using light and scanning electron microscopy, the morphology of the different structures of the tarsus of G. portentosa was analysed. Using an Instron® universal testing machine, a series of peak force experiments were then conducted to record the force required to lift the cockroaches off different substrates. G. portentosa was pulled off 10 different substrates, which consisted of smooth Perspex; Perspex scored at 1cm intervals; Perspex hatched at 1 cm, 0.5 cm, and 1 mm intervals; Perspex abraded with fine grade sandpaper; Perspex abraded with coarse grade sandpaper; wood; glass; and Teflon. A clear relationship was seen where an increase in scoring on the Perspex caused a decrease in adhesive ability of G. portentosa. This may be due to there being adequate contact area for the attachment of the pads and to allow the claws to engage. The results obtained suggest that to achieve the greatest adhesion to substrates, G. portentosa uses a combined effect of both adhesive pads and pretarsal claws. Adhesion to a wide range of substrates appears to be an adaptation to life as a wingless forest floor dweller.